DIRECT EFFECT OF COMORBID MENTAL DISORDERS ON THE CLINICAL COURSE OF ALCOHOLISM - Akmal Axmadjonovich, Gaybiyev; Mavludaxon Mirxamzayevna, Mamurova; Bobir Temirpulotovich, Turayev (PT. Antis International Publisher, 2025)
Objective: This study aims to investigate the direct effect of comorbid mental disorders on the clinical course of alcoholism, emphasizing the complexities involved in diagnosis, treatment, and rehabilitation. Method: A comprehensive analysis was conducted through a cross-sectional study involving patients diagnosed with alcohol use disorder (AUD) and co-occurring mental health conditions. Data were collected using standardized psychiatric assessments and clinical evaluations from both narcology and psychiatry specialists. Results: The findings reveal that the presence of comorbid mental disorders significantly exacerbates the severity and chronicity of alcoholism, leading to poorer treatment outcomes, increased relapse rates, and heightened resistance to standard therapeutic interventions. Patients with dual diagnoses exhibited more complex clinical profiles, necessitating integrated and multidisciplinary treatment approaches. Novelty: This study highlights the critical need for dual-specialist involvement in the management of AUD with comorbid mental disorders, offering new insights into integrated treatment frameworks that can enhance clinical outcomes and reduce the burden of relapse.